2016
DOI: 10.1177/1363461516632389
|View full text |Cite
|
Sign up to set email alerts
|

“The sun has set even though it is morning”: Experiences and explanations of perinatal depression in an urban township, Cape Town

Abstract: This study examined experiences and explanations of depression amongst Xhosa-speaking pregnant women, mothers, and health workers in an urban township in Cape Town, South Africa. The study was conducted as part of formative research for a randomised controlled trial to develop and evaluate a task-sharing counselling intervention for maternal depression in this setting. We conducted qualitative semistructured interviews with 12 depressed and 9 nondepressed pregnant women and mothers of young babies, and 13 heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
62
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(71 citation statements)
references
References 64 publications
9
62
0
Order By: Relevance
“…While attention has focused on physical changes and discomfort during pregnancy, far less has been paid to women’s emotional, economic, and social well-being [40], especially in African settings [but see 13,14,30,41, 42]. In women’s narratives, a dominant theme was that pregnant women at times felt vulnerable and emotionally alone, and sometimes were unable to identify what was bothering them or had no one with whom to discuss what was going on in their lives [40,43].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…While attention has focused on physical changes and discomfort during pregnancy, far less has been paid to women’s emotional, economic, and social well-being [40], especially in African settings [but see 13,14,30,41, 42]. In women’s narratives, a dominant theme was that pregnant women at times felt vulnerable and emotionally alone, and sometimes were unable to identify what was bothering them or had no one with whom to discuss what was going on in their lives [40,43].…”
Section: Discussionmentioning
confidence: 99%
“…Financial challenges [44] and marital status [46] were issues that we anticipated from our participants and other studies [14,41,54]. Many of the women interviewed had limited sources of income to sustain them, but although they spoke about their need for money, this was not the primary support that they identified they needed from their relationships and in pregnancy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, Davies et al (2016) found that women living in South African townships used "idioms of distress" to describe symptoms of their depression. Women described their depression as the "sun setting on them" or as "suppression of the brain".…”
Section: Symptoms Of Perinatal Depressionmentioning
confidence: 99%